2019
DOI: 10.1002/slct.201901519
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Y‐Zeolite with Zirconium for Enhancing the Active Component Loading: Preparation and Sulfate Adsorption Performance of ZrO(OH)2/Y‐Zeolite

Abstract: Nowadays, several techniques have been utilized to remove sulfate from industrial sewage. The method using ZrO(OH)2 to adsorb sulfate is highly efficient and environmentally friendly, however, nano‐powdered ZrO(OH)2 is hard to be recycled owing to its great loss in the adsorption process, which brings enormous difficulties to industrial applications. In this research, to prevent adsorbents from losing, Y‐zeolite was modified with zirconium, including the incorporation of zirconium as heteroatoms into zeolite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
4
5
0
Order By: Relevance
“…The results confirmed that the surface area of the synthesized sample is 483.4 m 2 /g. Furthermore, the result of BET analysis showed that the surface area of the synthesized HY-zeolite agrees with the standard BET values of HY-zeolite [32,[37][38].…”
Section: Bet Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The results confirmed that the surface area of the synthesized sample is 483.4 m 2 /g. Furthermore, the result of BET analysis showed that the surface area of the synthesized HY-zeolite agrees with the standard BET values of HY-zeolite [32,[37][38].…”
Section: Bet Resultssupporting
confidence: 71%
“…This introduction of Zr metal enhanced the activity and selectivity of the Cat-3 bimetallic catalyst Cat-3. This interpretation of the loaded metal's behavior was further supported by other researchers [22][23][24][25]38]. The Cat-3 catalyst simultaneously took advantage of the electronic and catalytic properties of the Zr and Pt metals to enhance its novel catalytic features, reaching a yield of isomers close to that of Cat-2 containing 2 wt% Pt.…”
Section: Catalytic Activity Testingsupporting
confidence: 55%
“…In addition, the surface area of the HY-zeolites loaded with metals showed a decrease in the surface area, taking into account that the zirconium-loaded catalyst had a higher surface area than the platinum-loaded catalyst. The reason for this is that the metal atoms may have closed some of the zeolite pores, and this is identical to what has been documented [40]. In addition, the bimetallic catalyst (Cat-9) had a surface area of 291.9 m 2 /g, as it was loaded with two types of metals.…”
Section: Bet-surface Area Analysissupporting
confidence: 74%
“…The peak wavenumber 983.7 cm -1 can be assigned to the antisymmetric stretching vibration of Si-O. The absorption bands at 770, 678, 574, and 480 cm -1 can be ascribed to an O-Si-O stretching vibration, Si-O symmetrical stretching vibration, O-Al-O stretching vibration, and Si-O-Si bending vibration, respectively, as well as the 1427 cm -1 band assigned to the bending vibration of NH + 4 [40,[44][45][46].…”
Section: Fourier-transformed Infrared Spectroscopy (Ft-ir) Analysismentioning
confidence: 97%
“…The absorption peak at 469 cm À1 could be assigned to the Si-O bond bending vibration of zeolite. The peak at 550 cm À1 for Si-O-Al stretching vibration and the absorption peak around 1,000 cm À1 appeared due to the anti-symmetric stretching vibration of the Si-O-Si bond (Ma et al 2019). The weaker absorption peak at 1,650 cm À1 could be assigned to the vibration of the water hydroxyl group, adsorbed by the zeolite, while the peak at 3,426 cm À1 belongs to the vibration absorption peak of the water molecules absorbed by the zeolite.…”
Section: Resultsmentioning
confidence: 99%